The current situation and influencing factors of posttraumatic growth in parents of children with autism: a qualitative study - Ming Hong; Sansan Lv (BMC Psychology)
Abstract Background There is relatively little research in China on the current situation and influencing factors of PTG of parents of children with autism, and the research conclusions are inconsistent. Quantitative research is difficult to deeply depict the dynamic process of PTG of parents of children with autism, and cannot deeply explore the main factors affecting PTG. However, qualitative research has a unique advantage in this regard. Methods 15 parents of autistic children from China participated in the present study. Data collected by one to one in-depth interview which was analyzed by thematic analysis. Results Four themes yielded. They are: significant increase in personal strength; significant improvement in interpersonal relationships; continuously deepening life perception; worry and confusion about the child’s future. The main influencing factors of PTG of parents of autistic children include the support of significant others and the partners, family income, cultural context, social reality and parents’ roles.Parents who experience traumatic events value money more than before, which is different from previous research findings. Conclusions The current status and influencing factors of PTG of Chinese parents of autistic children are different from existing research results and have the characteristics of Chinese cultural context. However, more research results are needed to test it.